Freedom of Religion in India: A Socio-Legal Perspective on Forced Conversions (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
A comprehensive analysis of the socio-legal dimensions of religious freedom in India, with a particular focus on the contentious issue of forced conversions. It begins by exploring the historical context of religious tolerance in India, tracing the evolution of religious freedom from the colonial period to the present day. The Indian Constitution guarantees the right to freedom of religion under Articles 25 to 28, which are designed to protect individuals' rights to profess, practice and propagate their religion while ensuring that public order, morality and health are not compromised. The challenges posed by forced conversions, which involve coercion, undue influence, or fraudulent means to induce religious conversion. It examines the legal framework established by various states in India through "Freedom of Religion" laws, aimed at preventing forced conversions and highlights the critical judicial interpretation of these laws. The Supreme Court's ruling in Stanislaus vs. State of Madhya Pradesh (1977) upholding the validity of anti-conversion laws is particularly significant in this context.